N′-(5-Bromo-2-hydroxybenzylidene)-3,4,5-trihydroxybenzohydrazide dihydrate - Alhadi, Abeer A.; Ali, Hapipah Mohd; Puvaneswary, Subramaniam; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The title compound, C14H11BrN2O5·2H2O, crystallizes as hydrogen-bonded sheets. The 2-hydr-oxy group on the benzyl-idene group forms an intra-molecular hydrogen bond to the N atom of the C=N double bond. The amino N atom is a hydrogen-bond donor to a water mol-ecule. The hydr-oxy group on the benzohydrazide group is a hydrogen-bond donor to one acceptor site, whereas each water mol-ecule is a hydrogen-bond donor to two acceptor sites.